Prus versus Świętochowski w sporze o naukowość, krytykę pozytywną i „Lalkę” - Sobieraj, Tomasz (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2008)
Volume I of the series Critical Literary Argument in Poland presents the genesis and history of an argument which was held in 1890 between the most prominent novelist of the period of positivism, Bolesław Prus, and a leading critic and ideologist of the camp of the positivists – Aleksander Świetochowski. The discussed argument touched upon several spheres: the ideological questions, the concept of positivist science, critical literary issues as well as the literary output of Prus, primarily his novel Lalka (“The Doll”).
An Argument about Scientific Character, Positivist Criticism and „The Doll”
Keywords: Bolesław Prus; Aleksander Świętochowski; Lalka; polemika krytycznoliteracka